The challenge of future landfill: a case study of Malaysia - Syed Ismail, Sharifah Norkhadijah; Abdul Manaf, Latifah (Academic Journals, 2013)
Landfilling is the most frequent waste disposal method worldwide. It is recognised as being an important option both now and in the near future, especially in low- and middle-income countries, since it is the easiest and the cheapest technology available. Owing to financial constraints, landfills usually lack of environmental abatement measures, such as leachate collection systems and lining materials. As a result, a lot of contamination is inflicted upon the environment. Importantly, even with proper abatement measures in landfills, there is no guarantee that contamination will be prevented. Another major concern is the appropriate location for landfills to ensure the impact towards the environment are minimised. This paper highlights the challenge to find suitable place for future landfill in Malaysia. There is a tendency of landfill to be built on unsuitable area such as near to residential area or on agricultural land where most of the land are grading as high prospect value to be developed as business or industrial area that are more profitable.